2005
DOI: 10.1109/tps.2005.856502
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the total ion flux from vacuum arc cathode spots

Abstract: -The ion flux from vacuum arc cathode spots was measured in two vacuum arc systems. The first was a vacuum arc ion source which was modified allowing us to collect ions from arc plasma streaming through an anode mesh. The second discharge system essentially consisted of a cathode placed near the center of a spherically shaped mesh anode. In both systems, the ion current streaming through the mesh was measured by a biased collector. The mesh anodes had geometric transmittances of 60% and 72%, respectively, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(49 citation statements)
references
References 24 publications
6
39
1
2
Order By: Relevance
“…Even as only a small percentage of ions do not stick, the flux of atoms (i.e., neutralized former ions) from the surface causes a very relevant density according to   1 a c ii a n S nv v   (28) since the characteristic atom velocity a v is much smaller than the characteristic ion velocity i v . Nonsticking necessarily produces neutrals, and charge exchange reactions (27) occur, predominantly reducing the fraction of higher charged ions and producing more singly charged ions, in agreement with measurements [100,102].…”
Section: Charge Exchange Collisionssupporting
confidence: 83%
“…Even as only a small percentage of ions do not stick, the flux of atoms (i.e., neutralized former ions) from the surface causes a very relevant density according to   1 a c ii a n S nv v   (28) since the characteristic atom velocity a v is much smaller than the characteristic ion velocity i v . Nonsticking necessarily produces neutrals, and charge exchange reactions (27) occur, predominantly reducing the fraction of higher charged ions and producing more singly charged ions, in agreement with measurements [100,102].…”
Section: Charge Exchange Collisionssupporting
confidence: 83%
“…These results can be taken as a refinement of the often-quoted value of about 10% [49]- [51]. The ion erosion rate experiments have been described in more detail elsewhere [52].…”
Section: B Ion Erosion Ratesupporting
confidence: 57%
“…Interestingly, we note that the Mevva-V ion source has been operated as a high current electron source by simply changing the source bias from positive to negative [55], without any other change to the setup. The LBNL Mevva V ion source is used for a variety of research purposes including exploration of vacuum arc phenomena [46], [52], ion implantation into metals [56], semiconductors [57] and optoelectronic materials [58], synthesis of high-Tc superconductors, some bioengineering experiments [59], heavy ion fusion [60], and other. This source has been fully described in [10], [30], [61], [62].…”
Section: A Mevva V (Lbnl Berkeley Usa)mentioning
confidence: 99%
“…Ions have been collected by negatively biased probes placed in some macroscopic distance (for example, see companion paper [49]). Early measurements by Smeets and Schulpen [8] indicated that the Fourier amplitude is MS#TPS0860.R1, --LBNL-56776 --~1 f β with 1 β ≈ , for frequencies up to 15 MHz, and 0 β = at higher frequencies.…”
Section: (Iv) Random Colored Noise In Ion Currentmentioning
confidence: 99%